Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatakan Hasil Belajar IPS Siswa Kelas III SD Negeri Ciputih 01 - Nuraeni, Cucu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to improve student learning outcomes in social studies subjects in class III by applying the Problem Based Learning (PBL) learning model with the help of image media. The research that was conducted was Classroom Action Research (CAR) which was carried out in two cycles of action, each cycle consisting of two meetings. The stages for each cycle are planning, implementation, observation and reflection. Data was collected using test and non-test techniques. The results of the first cycle of research showed that 60% of students who completed the post-test were completed. In the implementation of the second cycle of students who completed after carrying out the post test was 95%. These results indicate that the application of the Problem Based Learning (PBL) learning model with the help of image media can improve student learning outcomes in Social Sciences Class III subjects at SD Negeri Ciputih 01.